Performance Analysis of a Solar Heating Ammonia Decomposition Membrane Reactor under Co-Current Sweep - Tianchao Xie; Shaojun Xia; Jialuo Huang; Chao Wang; Qinglong Jin (Membranes, 2022)
Ammonia is an excellent medium for solar thermal chemical energy storage and can also use excess heat to produce hydrogen without carbon emission. To deepen the study of ammonia decomposition in these two fields, finite-time thermodynamics is used to model a solar-heating, co-current sweeping ammonia decomposition membrane reactor. According to the needs of energy storage systems and solar hydrogen production, five performance indicators are put forward, including the heat absorption rate (HAR), ammonia conversion rate (ACR), hydrogen production rate (HPR), entropy generation rate (EGR) and energy conversion rate (ECR). The effects of the light intensity, ammonia flow rate, nitrogen flow rate and palladium membrane radius on system performances are further analyzed. The results show that the influences of the palladium membrane radius and nitrogen flow rate on reactor performances are very slight. When the light intensity is increased from 500 W/m2 to 800 W/m2, the ACR, EGR, HAR and HPR increase obviously, but the ECR decreases by 14.2%. When the ammonia flow rate is increased by 100%, the ECR, EGR and HPR increase by more than 70%, the HAR increases by 15.6% and the ACR decreases by 12.9%. At the same time, the ammonia flow rate needs to be adjusted with the light intensity. The results can provide some guiding significance for the engineering application of ammonia solar energy storage systems and solar hydrogen production.